Utilisation of Video Media to Improve Student Learning Outcomes in PAI Learning in Class IV SDN 11 Palaluar - Afriyanto (BiCED Proceeding, 2024)
This study aimed to improve students' learning outcomes in Islamic Religious Education (PAI) by utilizing video media and the Discovery-Based Learning (DBL) approach. The research was conducted in two cycles involving fourth-grade students at SDN 11 Palaluar. In the first cycle, the focus was on reading and memorizing Q.S. At-Tin, while the second cycle emphasized writing skills in Qur'anic verses. The results revealed that video media significantly enhanced students' motivation and comprehension. In the first cycle, the average score increased from 57.5 to 75.42, with a completion rate of 66.67%. In the second cycle, the average score improved to 80.42, with a completion rate of 83.33%. The DBL model was also effective in actively engaging students in the learning process. This study concludes that integrating video media and DBL positively impacts students’ learning outcomes, particularly in reading, memorizing, and writing Qur'anic verses.